Gene doping: Present and future - Araujo Cantelmo, R.; Pereira Da Silva, A.; Teixeira Mendes-Junior, C.; Junqueira Dorta, D. (European Journal of Sport Science, 2020)
Being an elite athlete is an extremely coveted position, which can lead an individual to use doping. As knowledge is extended, doping techniques have become increasingly sophisticated, and the newest method of doping is gene doping. This article aims to present an updated bibliographic survey that addresses gene doping between 1983 and 2018. Anti-doping agencies have not yet approved any detection technique for this type of doping. The possibility of eradicating such doping is almost zero mainly because gene therapy advances rapidly. In this scenario, the future of gene doping must be discussed and decided before irreversible limits are exceeded. Keywords: Doping in sports, sports, gene doping, gene therapy, genes